STRATEGI CONTENT MARKETING INSTAGRAM DAN TANTANGANNYA DALAM MEMPERTAHANKAN CUSTOMER ENGAGEMENT - Fard, Ahmad Muhlis Fanmaddamkhul; Vania, Amelindha (JURNAL LENTERA BISNIS, 2025)
This study aims to determine the implementation of Instagram content marketing strategies and the challenges in maintaining customer engagement. This study uses a descriptive qualitative approach. The research subjects consisted of four informants divided into two categories: internal and external subjects. The data used included primary and secondary data collected through interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman method, which includes data reduction, data presentation, and conclusion and verification stages. The results of this study indicate that the implementation of the Instagram content marketing strategy @ngopibarengpintulangit has adapted content to the needs of the audience, especially the family segment, through the use of various Instagram features. The transition from soft selling to hard selling was carried out to encourage direct audience decisions, but the consistency of uploads, caption development, and suboptimal two-way interaction resulted in uneven engagement levels.